Next-generation multiplex food allergen sensing: From PDMS microfluidic prototypes toward intelligent industrial systems - Xin Zhao; Mengfei Deng; Yuhao Huang; Wenjia Zhu; Lili Xu; Hong Lin; Zhenxing Li (Trends in Food Science & Technology, 2026)

Unraveling the impact of food processing technologies on postbiotic bioactivity, food matrix interactions, and human health outcomes - Junxin Zhao; Mengfei Duan; Ruiying Xu; Yumeng Cheng; Jinheng Li; Deguo Wang; Xianghui Yan; Ping Yu; Zheling Zeng; Yunzhi Lin; Yoshimitsu Masuda; Ken-ichi Honjoh; et al. (Food Bioscience, 2026)

Intracranial Mitochondrial Microparticles Promote Cerebral Edema via Endothelial Injury in Stroke - Xiaoyan Du; Xintong Yu; Mengfei Wang; Ying Fu; Kunxin Lin; Jiaying Wu; Qianqian Lin; Wenlong Zhao; Yi Lin (Translational Stroke Research, 2026)

Ce-Fe bimetallic zeolite-imidazolate framework catalyzed ozonation for enhanced tetracycline degradation: synergistic electron transfer and multi-radical reaction pathways - Lin Yue; Shiqi Xing; Mengfei Wang; Hongxue An; Yunlong Yao; Yuxuan Li; Jing Lian (Environmental Research, 2026)

Treatment of Kiwifruit with Bacillus subtilis LS11 postharvest mitigates disease occurrence and alters its microbiome - Huiyun Song; Zhihao Duan; Jian Yang; BeiBei Liang; Honghui Shi; Xiaoling Wang; Zhu Gao; Liuyi Pan; Jipeng Mao; Xuchen Gong; Dongliang Yao; Mengfei Lin (Postharvest Biology and Technology, 2026)

Expression, characterization and antibacterial effects of two endolysins as novel biocontrol agents against Pseudomonas oleovorans in foods - Junxin Zhao; Tonglei Zhou; Yiming Xu; Mengfei Duan; Zheng Zhao; Jingyi Gui; Didi Guo; Xinshuo Yang; Deguo Wang; Yunzhi Lin; Su Zar Chi Lwin; Yoshimitsu Masuda; et al. (International Journal of Food Microbiology, 2026)

Step-by-step assembly of functionalized chitosan films via NADES and caffeic acid / ferulic acid grafting for walnuts preservation - Yaoqi Zhang; Qianwei Lin; Karthikeyan Venkatachalam; Mengfei Mao; Wanfeng Wu; Nannan Dong; Zisheng Luo; Zhaojun Ban; Li Li (Food Hydrocolloids, 2026)

How do salt-tolerant granular sludge cultivated under different conditions carry out nitrogen and phosphorus removal? - Mengfei Wang; Junguo He; Ruimiao Zhang; Lin Li; Jie Zhang (Environmental Research, 2025)

Oxidative pyrolysis of biomass waste: Efficient production of humic substances with enhanced agricultural potential and environmental benefits - Jian Li; Wen Fu; Xiaowei Bai; Ning Mao; Xiangrui Lin; Heping Yang; Mengfei Wang; Guangxuan Liu; Zhenghua Dai (Journal of Cleaner Production, 2025)

Integrated metabolomics and transcriptomics reveal the nutritional profiles and molecular mechanisms in colored cauliflowers - Xiaoguang Sheng; Mengfei Song; Jiansheng Wang; Huifang Yu; Yusen Shen; Shuting Qiao; Fan Lin; Sifan Du; Honghui Gu (Food Bioscience, 2025)

Enhanced peroxymonosulfate activation by Co/Mn and P modified carbon nitride for ciprofloxacin degradation: Performance, mechanism and toxicity assessment - Bingfeng Lin; Guanghui Liu; Zhijia Zheng; Haiyang Shi; Mengfei Zhang; Xi Yuan; Yingping Huang; Ruiping Li; Cilai Tang (Journal of Environmental Chemical Engineering, 2025)

Oxidative pyrolysis characteristics and exothermic heat release effects of cellulose, hemicellulose, and lignin - Jian Li; Wen Fu; Xiaowei Bai; Xiangrui Lin; Heping Yang; Mengfei Wang; Guangxuan Liu; Zhenghua Dai (Fuel, 2025)

Community prevention and standardized clinical treatment jointly improve cancer outcome: Real-world evidence from an esophageal cancer patient cohort study - Ji Ke; Fangfang Liu; Wei Yang; Ruiping Xu; Lei Chen; Wenlei Yang; Yu He; Zhen Liu; Bolin Hou; Liqun Zhang; Miaoping Lin; Lixin Zhang; et al. (Science Bulletin, 2024)

Fine mapping of a major co-localized QTL associated with self-incompatibility identified in two F2 populations (broccoli × cauliflower and cauliflower × Chinese kale) - Yusen Shen; Jiansheng Wang; Xiaoguang Sheng; Huifang Yu; Ranjan K. Shaw; Mengfei Song; Shiyi Cai; Shuting Qiao; Fan Lin; Honghui Gu (Theoretical and Applied Genetics, 2024)

Enhanced mass transfer by 3D printing to promote the degradation of organic pollutants in electro-Fenton system - Mingjie Lu; Shiyuan Lin; Xiaolin Ma; Zhenzhan Xu; Hao Yang; Mengfei Wang; Junxiu Piao; Jinqiang Zhang; Pei Dong; Chaocheng Zhao (Chemical Engineering Journal, 2024)

Temperature distribution evolution in zero-gap alkaline water electrolyzer: Experimental and modeling - Mengfei Zhang; Lingyu Gao; Lin Yang; Guixuan Shan; Yuxuan Wang; Xinyi Huo; Wei Li; Jinli Zhang (Fuel, 2024)

Integrated analysis of miRNAs, transcriptome and phytohormones in the flowering time regulatory network of tea oil camellia - Haixiao Fan; Xiaoling Wang; Huiqi Zhong; Kehui Quan; Ruohan Yu; Shiying Ma; Siqiong Song; Mengfei Lin (Physiology and Molecular Biology of Plants, 2024)

Discovery of the tigecycline resistance gene cluster tmexCD3-toprJ1 in Pasteurella multocida strains isolated from pigs in China - Congcong Shi; Zhanwei Zhu; Yuyao Shang; Wenbo Song; Jie Yang; Haixin Bi; Zihao Wang; Rui Xie; Mengfei Zhao; Lin Hua; Huanchun Chen; Bin Wu; et al. (Veterinary Microbiology, 2024)

Postharvest treatment with Bacillus velezensis LX mitigates disease incidence and alters the microbiome on kiwifruit surface - Zhihao duan; Huiyun Song; Honghui Shi; Zhu Gao; Jipeng Mao; Yunpeng Cao; Heqiang Huo; Juncheng Li; Xiaoling Wang; Mengfei Lin (Postharvest Biology and Technology, 2024)

Efficient activation of peroxymonosulfate by Co/Cu co-substituted-ferrite and carbon composite for rapid degradation of tetracycline in aqueous phase: Performance evaluation and mechanisms - Bingfeng Lin; Cilai Tang; Zhijia Zheng; Mengfei Zhang; Yingping Huang; Xi Yuan; Xiaohong Liu; Yonghong Wu (Chemical Engineering Journal, 2024)

Plasmonic array assisted mass spectrometry for preferential metabolite detection - Xvelian Li; Wei Chen; Mengyi Wu; Wenjun Yu; Mengfei Wang; Minjia Niu; Fanyu Meng; Yuewei Zhao; Ahmed Osman; Nahla O. Mousa; Hui Shi; Kun Qian; et al. (Chemical Engineering Journal, 2024)

Novel cytochrome P450s for various hydroxylation of steroids from filamentous fungi - Guojuan Yi; Hanlu Zou; Tao Long; Tolbert Osire; Lin Wang; Xiaoyun Wei; Mengfei Long; Zhiming Rao; Guojian Liao (Bioresource Technology, 2024)

High propensity of membrane fouling and the underlying mechanisms in a membrane bioreactor during occurrence of sludge bulking - Mengfei Wu; Meijia Zhang; Liguo Shen; Xinhua Wang; Deng Ying; Hongjun Lin; Renjie Li; Yanchao Xu; Huachang Hong (Water Research, 2023)

Comparative transcriptome analysis provides insight into the molecular mechanisms of long-day photoperiod in Moringa oleifera - Mengfei Lin; Shiying Ma; Kehui Quan; Endian Yang; Lei Hu; Xiaoyang Chen (Physiology and Molecular Biology of Plants, 2022)

Climate warming promotes deterministic assembly of arbuscular mycorrhizal fungal communities - Xinyu Xu; Yunpeng Qiu; Kangcheng Zhang; Fei Yang; Mengfei Chen; Xi Luo; Xuebin Yan; Peng Wang; Yi Zhang; Huaihai Chen; Hui Guo; Lin Jiang; et al. (Global Change Biology, 2022)
Arbuscular mycorrhizal fungi (AMF) significantly contribute to plant resource acquisition and play important roles in mediating plant interactions and soil carbon (C) dynamics. However, it remains unclear how AMF communities respond to climate change. We assessed impacts of warming and precipitation alterations (30% increase or decrease) on soil AMF communities, and examined major ecological processes shaping the AMF community assemblage in a Tibetan alpine meadow. Our results showed that warming significantly increased root biomass, and available nitrogen (N) and phosphorus (P) in soil. While precipitation alterations increased AMF abundances, they did not significantly affect the composition or diversity of AMF communities. In contrast, warming altered the composition of AMF communities and reduced their Shannon–Wiener index and Pielou's evenness. In particular, warming shifted the AMF community composition in favor of Diversisporaceae over Glomeraceae, likely through its impact on soil N and P availability. In addition, AMF communities were phylogenetically random in the unwarmed control but clustered in warming plots, implying more deterministic community assembly under climate warming. Warming enhancement of root growth, N and P availability likely reduced plant C‐allocation to AMF, imposing stronger environmental filtering on AMF communities. We further proposed a conceptual framework that integrates biological and geochemical processes into a mechanistic understanding of warming and precipitation changes’ effects on AMF. Taken together, these results suggest that soil AMF communities may be more sensitive to warming than expected, highlighting the need to monitor their community structure and associated functional consequences on plant communities and soil C dynamics under the future warmer climate.

Gene UCHL1 expresses specifically in mouse uterine decidual cells in response to estrogen - Lishuang Hao; Di Song; Mengfei Zhuang; Yan Shi; Lin Yu; Yaping He; Jian Wang; Tingting Zhang; Zhaogui Sun (Histochemistry and Cell Biology, 2020)

Evolution and expression patterns of the trehalose-6-phosphate synthase gene family in drumstick tree (Moringa oleifera Lam.) - Mengfei Lin; Ruihu Jia; Juncheng Li; Mengjie Zhang; Hanbin Chen; Deng Zhang; Junjie Zhang; Xiaoyang Chen (Planta, 2018)